PENGEMBANGAN INFRASTRUKTUR DIGITALISASI DESA MENDUKUNG DESA WISATA DAN TEKNOLOGI SOLAR CELL DESA - nurul umam; Ragil Wirantono; Aditya Rifansa; Ikhsan Setiawan (Jurnal Abdi Daya, 2022)
Agricultural infrastructure is the key in the main business field to support the economic growth of the village. The geographical area of Banjarsari Village is a lowland inundated with swamp water adjacent to the Bengawan Solo river, the border of the Jombang Regency area with Nganjuk Regency, a population of 49,959 people, rice fields with an area of 241.79 ha, agricultural production in the form of rice paddy fields and fields with a harvest area of 3,471.1 tons, corn production of 320.1 tons, plantation production of 2,436.09 tons. This shows the strength of Banjarsari Village in Agriculture and Animal Husbandry, very important supported by infrastructure and access to agricultural technology, modern agricultural irrigation infrastructure, especially the use of renewable energy technology that has zero agricultural electrification costs The purpose of implementing this KKN is to lead rural communities to a more prosperous life and help improve the social conditions of rural communities and make villages better known in terms of tourism and village MSMEs. The method in implementing this KKN is by interviewing and field observation methods.